Cytotoxic arylnaphthalide lignan glycosides from the aerial parts of Phyllanthus taxodiifolius - Patoomratana Tuchinda (2018)
The arylnaphthalide lignan glycosides, taxodiifoloside (1), cleistanthoside A (2), cleistanthin A (3) and cleistanthin A methyl ether (4), together with a triterpene, glochidone (5), have been isolated from the aerial parts of Phyllanthus taxodiifolius. The structures were established using spectral and chemical methods. Compounds 3 and 4, as well as the derivatives 2a and 3a exhibited potent cytotoxic activities with GI50values in the range of 10-7-10-9M in five cultured mammalian cancer cell lines while the new compound 1 showed moderate activity (GI50in the order of 10-6M). Compounds 2 and 5 were inactive in all tested cell lines. © Georg Thieme Verlag KG Stuttgart.